2018
DOI: 10.1002/app.46915
|View full text |Cite
|
Sign up to set email alerts
|

Soluplus solutions as thermothickening materials for topical drug delivery

Abstract: Soluplus is a pharmaceutical excipient used primarily in the manufacture of solid dispersions. The polymer also exhibits interesting rheology in aqueous solution, increasing in viscosity as the solution is warmed. This material could have application topical drug delivery to sites including the skin, vagina, rectum or nasal mucosa, where the increase in viscosity allows for improved retention. However, there exists very little information surrounding this “thermothickening” phenomenon and the effect of solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 21 publications
1
25
1
Order By: Relevance
“…It is also possible that SP acts as somewhat of an irritant on the cell monolayer [39], causing the monolayer to tighten or the cells to start producing more mucus, therefore increasing the likelihood of an interaction with SP and, thus, finally decreasing the permeability of the paracellular marker. SP is reported to increase drastically in viscosity, forming a gel-like structure, partly because of the temperature and the effect of the salts present in the cell medium [32]. This viscosity-increasing effect was also demonstrated in this study.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…It is also possible that SP acts as somewhat of an irritant on the cell monolayer [39], causing the monolayer to tighten or the cells to start producing more mucus, therefore increasing the likelihood of an interaction with SP and, thus, finally decreasing the permeability of the paracellular marker. SP is reported to increase drastically in viscosity, forming a gel-like structure, partly because of the temperature and the effect of the salts present in the cell medium [32]. This viscosity-increasing effect was also demonstrated in this study.…”
Section: Discussionsupporting
confidence: 78%
“…The entanglement of micelles into a continuous gel network was found to be mainly an effect of temperature also influenced by the SP concentration and type of medium. Other authors have also reported on the effect of temperature and salts on the viscosity of SP [32]. Nevertheless, the results from dynamic light scattering clearly showed that at 25 °C, the micelles were monodispersed with similar size of 60–80 nm in all three media at a low concentration of SP (5%).…”
Section: Discussionmentioning
confidence: 82%
“…One often‐cited reason for this lack of translation is a belief that PNIPAM is cytotoxic, which is often used as a justification to explore alternative polymers displaying LCSTs. [ 143–147 ] There are, however, many studies demonstrating that a variety of cell lines remain viable in the presence of PNIPAM. [ 148–150 ] Cytotoxicity arising from PNIPAM has sometimes been attributed to its hydrolysis products,.…”
Section: Thermoreversible Gelatorsmentioning
confidence: 99%
“…The thermogelling properties of Soluplus in water, ethanol, and water, a range of phosphate buffered saline solutions and sodium chloride solutions have been studied. [ 145 ] The Soluplus solutions with concentrations greater than 20% were found to form gels with G′ maxima greater than ≈500 Pa. Increasing the concentration of Soluplus from 20 to 40% resulted in a decrease in gelation temperature from 40 to 37.5 °C. Preparing the same Soluplus formulations in 25% ethanol:water mixtures led to a decrease in G′ maxima to ≈10 Pa and prevented the formation of a gel (G′ > G″).…”
Section: Thermoreversible Gelatorsmentioning
confidence: 99%
“…Two methods reported in the literature are the mixing of other hydrophilic polymers into P407 solutions, or by covalently modifying the structure of P407. Key parameters which may affect the performance of P407 as a dosage form are the sol–gel transition temperature (Tgel), the rheology of the gel formed, dissolution rate, and the ability of the gel to adhere to mucosal membranes (mucoadhesion) . Other parameters which may be of interest are rate of drug release from the gel, ability to retard or promote permeation through membranes, and ability to solubilize hydrophobic drugs, but these parameters are outside of the scope of this review.…”
Section: Poloxamer 407 As a Thermogelling Materialsmentioning
confidence: 99%